IMPLEMENTASI PENGGUNAAN MODUL TRIGONOMETRI DENGAN PENDEKATAN PENEMUAN TERBIMBING TERHADAP MINAT BELAJAR SISWA KELAS X - Indah Nopita Sari; Krisdianto Hadiprasetyo; Erika Laras Astutiningtyas (Jurnal AlphaEuclidEdu, 2022)
This research includes descriptive research with a qualitative approach. The subjects in this study were mathematics teachers, and class X students of SMK Bina Patria 1 Sukoharjo in the 2021/2022 academic year. The object of this research is the implementation of the use of a trigonometry module with a guided discovery approach to students' interest in learning. Data collection techniques using interviews and questionnaires. From the results of research conducted, students' interest in learning obtained an average percentage on the aspect of feeling happy of 70.44% including the "high" criteria, on the interest aspect getting a percentage of 85.42% including the "very high" criteria, on the involvement aspect obtained a percentage of 73.44% included in the "high" criteria. In the aspect of independence, the percentage of 86.72% is included in the "very high" criteria. All aspects accumulated to obtain a percentage of 79.01% which is included in the "high" criteria. So it can be interpreted that the student's response to the implementation of the use of the module is good and increases student interest in learning so that the module is well used for learning mathematics. However, there are some obstacles, namely students still need adjustments when they first use the module and there are slight revisions or improvements in certain parts in order to produce a better module, making it easier for readers to use it.